Firm-level versus sector-level trade Unions: The role of rent-sharing motives - Marco De Pinto (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2015)
What are the effects of firm- and sector-level trade unions on unemployment and aggregate output if individuals have rent-sharing motives? To answer this question, we extend a Melitz-type model to unionized labor markets. Because individual rent-sharing motives are only taken into account and asserted by firm-level unions which capture a higher fraction of firms' rents via firm-specific wages, average profits are higher under sector-level trade unions. As a consequence, firm-selection increases (relative to firm-level unions), which causes average marginal costs to decline. At the general equilibrium, labor demand then, ceteris paribus, increases and unemployment falls. This new mechanism interacts with the negative employment effect due to higher wage markups of sector-level trade unions, as shown e.g. by Calmfors et al. (1988). Simulating our model indicates that the unemployment damping effect of rent-sharing motives mitigates but does not compensate for the unemployment increase caused by higher wage markups, while aggregate output is higher under sector-level agreements.
Keywords: J3; J51; J6; 330; Trade Unions; Rent-sharing Motives; Bargaining Level; Heterogeneous Firms; Unemployment